Co-creation of innovative experiences in the Spanish e-Administration - Belén Álvarez-Crespo (Responsibility and Sustainability, 2014)
The need to eliminate the existing gap between technological development of e-Government and the development of use by the citizenship forces to raise new approaches. On this basis, this paper explores several concepts which are key factors for a full development of e-Government.